Teleworking in Romania during Covid-19 crisis: From conjunctional adaptation to change of economic paradigm - Gavril (Moldovan), Ioana Andrada; Frățilă (Adam), Alexandra; Iacob, Silvia Elena; Lădaru, Georgiana-Raluca (Frontiers in Environmental Science, 2022)
The COVID-19 crisis has led to a raise in the number of people working remotely. This paper aims at identifying the extent to which the pandemic will determine a paradigm change regarding teleworking in Romania Our research is based on two surveys designed to assess the impact of teleworking both on individuals and on efficiency at the organizational level. The results show that, generally, teleworking has significant advantages, both for employees and employers. As we become aware of these advantages, it is quite likely that Romania will experience a paradigm shift in terms of teleworking, as both managers and employees consider that teleworking becomes a very good option. However, the changes will be gradual and with different intensities at the sectoral level, as teleworking must be adapted to the specificities of each sector or activity. While some sectors tend to make teleworking the new organizational culture, others will capitalize on the benefits of teleworking progressively, in relation to technological endowments and structural changes that will continue to occur. On the other hand, teleworking has the advantage of promoting the improvement of digital skills for employees, which is a great step forward for a higher degree of digitalisation.